2009
DOI: 10.1016/j.bcp.2008.08.031
|View full text |Cite
|
Sign up to set email alerts
|

The aryl hydrocarbon receptor cross-talks with multiple signal transduction pathways

Abstract: Exposure to toxic polycyclic aromatic hydrocarbons raises a number of toxic and carcinogenic responses in experimental animals and humans mediated for the most part by the aryl hydrocarbon---or dioxin---receptor (AHR). The AHR is a ligand-activated transcription factor whose central role in the induction of drug-metabolizing enzymes has long been recognized. For quite some time now, it has become clear that the AHR also functions in pathways outside of its role in detoxification and that perturbation of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
282
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(300 citation statements)
references
References 98 publications
(100 reference statements)
12
282
1
5
Order By: Relevance
“…The identification of kynurenine (Kyn) as an endogenous AhR ligand was a major impetus for in-depth investigation of AhR's previously unknown function in physiologic and pathologic events (10). Although recent studies have suggested a potential role of AhR in regulating cell proliferation, cell-cycle distribution, and cell apoptosis, the underlying mechanism is largely unknown (11).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of kynurenine (Kyn) as an endogenous AhR ligand was a major impetus for in-depth investigation of AhR's previously unknown function in physiologic and pathologic events (10). Although recent studies have suggested a potential role of AhR in regulating cell proliferation, cell-cycle distribution, and cell apoptosis, the underlying mechanism is largely unknown (11).…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional activation of the CYP1A1 gene is mediated by the binding of environmental pollutants (benzo[a] pyrene) to the cytosolic receptor ,aryl hydrocarbon receptor (AhR) and then translocates to the nucleus where it heterodimerizes with another protein aryl hydrocarbon nuclear tranlocator (ARNT). This heterodimer binds to consensus regulatory sequences termed as aryl hydrocarbon response elements (AhREs) located in the promoter region of AhR target genes such as CYP1A1 and CYP1A2 and initiate their transcription by recruiting RNA polymerase II (Puga et al, 2009). In addition to the well known positive regulation of CYP1A1, the expression of this gene is repressed by several agents and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Aryl hydrocarbon receptor was first discovered as a mediator of dioxin toxicity, but, at present, the AhR pathway is thought to have diverse roles in many cellular functions including the immune system. 2,3 The AhR pathway has been recently shown to be an important regulator of inflammation and immunity. 4,5 For instance, Ahr has an essential role in the negative regulation of the lipopolysaccharide (LPS) signaling pathway through interaction with Stat1.…”
mentioning
confidence: 99%